2021
DOI: 10.1038/s41598-021-81622-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel gene rearrangement in the mitochondrial genome of Muraenesox cinereus and the phylogenetic relationship of Anguilliformes

Abstract: The structure and gene sequence of the fish mitochondrial genome are generally considered to be conservative. However, two types of gene arrangements are found in the mitochondrial genome of Anguilliformes. In this paper, we report a complete mitogenome of Muraenesox cinereus (Anguilliformes: Muraenesocidae) with rearrangement phenomenon. The total length of the M. cinereus mitogenome was 17,673 bp, and it contained 13 protein-coding genes, two ribosomal RNAs, 22 transfer RNA genes, and two identical control r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Mitochondrial gene rearrangement is an important molecular marker and is considered to be an effective tool for studying mitochondrial evolution 26 . A large number of studies and results have shown that gene rearrangements in metazoan mitochondrial genomes are conserved 20 and the occurrence of gene rearrangements is relatively random and rare 1 , 19 , 20 , 27 . However, it can be used as direct evidence of evolutionary relationships between species 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial gene rearrangement is an important molecular marker and is considered to be an effective tool for studying mitochondrial evolution 26 . A large number of studies and results have shown that gene rearrangements in metazoan mitochondrial genomes are conserved 20 and the occurrence of gene rearrangements is relatively random and rare 1 , 19 , 20 , 27 . However, it can be used as direct evidence of evolutionary relationships between species 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial gene rearrangement is known as an effective phylogenetic signal for studying mitochondrial evolution [ 8 ]. Several studies and results have confirmed that gene rearrangements in metazoan mitochondrial genomes are conserved [ 33 ] and gene rearrangements occur relatively randomly and rarely [ 10 , 33 , 34 , 35 ]. However, it can be used as direct evidence of evolutionary relationships between species [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The origin of light chain replication (OL) was usually found within a WANCY group and can fold into a stem-loop ring secondary structure ( Zhang et al, 2021a ). The OL of G. dengba and G. tibetana were located between tRNA-Asn and tRNA-Cys with the same length of 34 bp, and 1 bp longer than G. yajiangensis (33 bp) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In general, the structure of the fish mitochondrial genome is extremely conserved ( Gong et al, 2013 ). With the gradual increase in mitochondrial DNA sequence data for fish, reports of mitogenome rearrangements continue to appear ( Miya et al, 2001 ; Inoue et al, 2003 ; Zhang et al, 2021a ). To date, a few models have been employed for mitochondrial gene rearrangement.…”
Section: Introductionmentioning
confidence: 99%